Colorado attitudes about agriculture and food: 2011 executive summary - Sullins, Martha, author; Thilmany-McFadden, Dawn, author; Songa, Dominique, author; Marconi, Nick, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2012)
This summary highlights some key findings of the 2011 Survey on Public Attitudes about Colorado Agriculture. The study's figures, tables and discussion are based on the responses of 504 Coloradans who participated in an online survey in August 2011.
June 2012.
Keywords: economics; agriculture; Colorado; grown products; quality of life; natural resources